Importance and performance of managerial training in Indian companies – an empirical study. Issue 2 (2014) - ,
Abstract : Purpose – The purpose of this paper is to compare the importance and performance of managerial training in India among different industrial sectors in the light of asynchronous industrial growth in last two decades which has unevenly touched various business organizations.Design/methodology/approach – For the purpose of analysis organizations are divided at two levels. At the first level, they are divided between multinational and Indian origin category and at the second level between service and manufacturing category. A 2×2 full factorial design with unequal numbers is used to analyze main as well as interaction impacts. A sample size of 542 is taken which comprises training professionals, top/general managers and trainee employees.Findings – Study concludes that Indian origin organizations fall short in terms of importance given and performance of training function compared to multinational companies. Further, it is found that service companies have an edge over manufacturing companies in terms of importance and performance of training.Research limitations/implications – Study is mainly focussed on large organizations in India and may not be representative of small organizations. The major implication is that Indian origin organizations as well as manufacturing organizations have to devote more time and financial resources to training to compete in the era of globalization.Practical implications – It is implied from the findings that a concerted effort by training professionals in Indian and manufacturing companies is required to improve the content as well as image of the training function to get the due attention and resources within the organization.Originality/value – The paper presents an original perspective on situation of training function in Indian organizations and will be of importance to training professionals and other stakeholders. Acknowledgements : The author would like to acknowledge the reviewers for their useful comments and suggestions.